STUDY OF MARINE ECOTOURISM POTENTIAL AT PANDARATAN BEACH, CENTRAL TAPANULI REGENCY, NOURTH SUMATRA PROVINCE - Muhammad Yusuf; Thamrin Thamrin; Joko Samiaji (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted in September 2019 to determine Pandaratan beach potential and development strategy as marine ecotourism destination in Central Tapanuli Regency, North Sumatera. Three sampling stations were surveyed. The results showed that suitability index value for beach recreation activities at station I was 90.38%, station 2 87.17% and station 3 88.47% included in the S1 category or very suitable for marine ecotourism respectively and The highest marine tourism suitability index value was located at Station I, This was supported by the open coastal land cover. The land suitability value for beach tourism activities range from 87.17 to 90.38% with an average value of 87.53%. The highest conformity value were found in stations 1 and 3, with the value of 90.38%, while the lowest suitability value was found in station 2, with the value of 87.17%.The perception of stakeholders showed that a number of 37% said that they strongly agree to develop the potential of marine ecotourism areas, 49% said  agree, 7% stated neutral, 3% said they did not agree and 2% stated strongly disagree respectively.Keywords: Central Tapanuli, Pandaratan Beach, Marine Ecotourism